A proposal for the unification of social protection benefits for children, youth and those vulnerable to poverty - Sergei Soares; Letícia Bartholo; Rafael Guerreiro Osorio (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
Social protection policy in Brazil is a historically built patchwork of programmes that pay different values to people in the same situation, leaves many unprotected (in particular, 17 million children) and is fraught with duplications and other inefficiencies. This paper proposes an approach through which all transfers to individuals vulnerable to poverty and children can be brought together within a single framework. The budgets of the Bolsa Família, Abono Salarial and Salário-Família programmes and the child income tax deduction together add up to BRL52 billion (about USD15 billion). With these resources, it is possible to propose a new transfer programme based on a universal child benefit and a targeted extreme poverty grant that will be twice as effective at reducing poverty and inequality as the four existing programmes
Keywords: 330; social protection; universal child grant; Bolsa Família; Abono Salarial; Salário-Família